Queer masculinities and colitud: experiences of Chilean men in the neoliberal context - Azócar González, Rodrigo (2022)
The neoliberal model of society, in full force but deeply questioned in Chile, puts in permanent tension the conservative configuration of a society structured under a deep misogynist and patriarchal root, facing the emergence and positioning of gender diversity as incident political subjects in a social context that is reorganized. The visibilization of the experiences of construction of queer masculinities is expressed in the stories of men born after the dictatorship and allow us to analyze the dimensions and scope of the neoliberal project in the identity configuration of the subjects organized under a colitud that recognizes the value of the marginal and excluded under this ideological context, will help to understand the dissident contexts, the community demands for recognition, the critical organization of difference and the deepening of the questions produced by the contexts of inequity, inequality, domination and subordination promoted by neoliberal values.